Alert [compact disc, unabridged] - Patterson, James, 1947-; Ledwidge, Michael (Patterson, James, 1947- Detective Michael Bennett thriller., 2015)
Someone is trying to bring New York to its knees. After a series of urban disasters throws daily life into utter chaos, the entire city is on high alert. Waiting for the next deadly domino to fall, Detective Michael Bennett, along with his old pal, the FBI's Emily Parker, have to catch the shadowy criminals who claim responsibility. In the wake of a shocking assassination, Bennett begins to suspect that these mysterious events are just the prelude to the biggest threat of all.